Praktik Kecantikan Tanpa Izin Sebagai Tindak Pidana: Upaya Hukum Dalam Pemulihan Kerugian Korban - Aurellia, Chyntia; Adhari, Ade (Legal Standing : Jurnal Ilmu Hukum, 2025)
The development of the beauty industry in Indonesia has contributed to the rise of illegal beauty practices carried out by non-medical personnel without official permits, which can jeopardize the health and safety of consumers. These unlicensed beauty practices constitute a violation of the Medical Practice Act, which prohibits non-medical service providers from performing medical procedures without authorization. This study aims to analyze unlicensed beauty practices as criminal acts and the legal avenues available for victims to seek compensation for damages. The research method employed is a literature review, analyzing regulations, scientific journals, and relevant cases. The results of the study show that unlicensed beauty practices not only violate administrative aspects but also pose significant health risks. Victims can seek compensation through criminal and civil legal channels; however, challenges in law enforcement and the low level of public legal awareness hinder recovery efforts. This study provides recommendations to improve supervision, strengthen regulations, and raise public awareness about the dangers of illegal beauty practices.